EVALUASI PROGRAM SISTEM KREDIT SEMESTER DI SMA NEGERI 1 SALATIGA - Hardini, Agustina Tyas Asri; Sulasmono, Bambang Suteng (Universitas Kristen Satya Wacana, 2016)
This study aimed to evaluate semester credit system program in SMA Negeri 1 Salatiga. This study was as evaluation research by using CIPP models (Context, Input, Process, and Product) along with qualitative descriptive approach. This data collected by interviews, documentations and observation. The data were analyzed by applying Miles and Huberman theory in Sugiyono (2013:95) that consisted of data collection; data reduction; data display; and conclusions. This study use triangulation technique to test the validity of data. The result showed that: 1) SMAN 1 Salatiga Semester Credit System Program implementation in context evaluation based on the needs of learners possess special smart categories; 2) SMAN 1 Salatiga Semester Credit System Program implementation in input evauation include the plan, mechanism implementation, teachers, learners, finance, infrastructure, and schedule are valued as sufficient; 3) SMAN 1 Salatiga Semester Credit System Program implementation in process evaluation have been carried out as planned program although there are still some obstacles, but have been already handled well; 4) SMAN 1 Salatiga Semester Credit System Program implementation in terms of the results were in accordance with the original purpose of the program, that was to facilitate learners with smart category Outstanding in order to complete their high school studies only for 2 years.